Impacts of large-scale hydroelectric dam development on ground-dwelling birds revealed by long-term camera trapping - Norfazliyana Nordin; Nor Adibah Ismail; Fudzla Zulfa Khiruddin; Ummi Nur Syafiqah Daud; Nurfatin Batrisyia Md Ali; Saiful Hilmi Jamal Shuhaily; Fatihah Najihah Arazmi; Ahmad Khusaini Mohd Kharip Shah; Aisah Shukor; Shukor Md Nor; Mohammad Saiful Mansor (Ecological Processes)
Abstract Background The increasing demand for large-scale hydroelectric dam development in tropical developing countries has led to significant land-use changes that impact biodiversity, particularly in megadiverse countries, such as Malaysia. Although many recent infrastructure projects incorporate sustainable concepts for wildlife monitoring and management, studies on the impacts of habitat fragmentation on ground-dwelling birds during the development phase remain scarce. This study aimed to assess the response of forest bird communities, particularly the ground-dwelling birds, across different phases of hydroelectric dam development using infrared camera traps. We collected data from 14 sampling sites in Nenggiri hydroelectric dam catchment area for 25 months across three developmental phases: pre-logging, logging, and construction. Results We recorded 1045 occurrences of 33 bird species, including the critically endangered Malayan Crestless Fireback Lophura erythrophthalma and the endangered Malayan Peacock-Pheasant Polyplectron malacense. There were significant changes between phases, with a notable decrease in the number of pheasants detected, such as the Great Argus Argusianus argus and Malayan Crested Fireback Lophura rufa, especially during the construction phase. Indicator species analysis (IndVal) identified seven species showing strong associations (p < 0.05) with specific development phases, including the Barred Cuckoo-Dove Macropygia unchall and Great Argus for the pre-logging phase. Conclusion These results highlight the vulnerability of ground-dwelling birds, particularly pheasants, to habitat disturbances from large-scale development activities. We propose incorporating camera trap assessments into major infrastructure projects to identify key locations of conservation-priority bird species, and to inform targeted rescue or translocation efforts, particularly during high-impact phases such as habitat clearance and dam impoundment.